PELAKSANAAN KEGIATAN KEPRAMUKAAN DI SLB PELITA HATI PEKANBARU - Japriadi '; Wilson '; Jaspar Jas Jas (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract. The formula of the research is “How the implementation of boyscouting in SLB Pelita Hati Pekanbaru?” based on the formula the purpose of the research was to know the implementation of boyscouting in SLB Pelita Hati Pekanbaru. Kind of the research was descriptive naturalistic that aim to know the implementation of boyscouting in SLB Pelita Hati Pekanbaru by systematically way about thing (Lexy J Maleong, 1989:191). Research site is at the SLB Pelita Hati Pekanbaru. The research concluded that the implementation of boyscouting in SLB Pelita Hati Pekanbaru consist of placement of implementation, time of implementation, matter of implementation and infrastructure of the implementation. Implementation of boyscouting done on Saturday and monday. While the time knows the implementation of boyscouting in SLB Pelita Hati Pekanbaru variated, sometimes 2 hours, even more. In the aspect of instructure or trainer in SLB Pelita Hati Pekanbaru were the experienced instructors especially in SLB Pelita Hati Pekanbaru. Based on the research generally that the implementation of boyscouting in SLB Pelita Hati Pekanbaru run well as hoped. Keywords: Implementation of boyscouting